HUBUNGAN PELAKSANAAN SATU RUMAH SATU JUMANTIK TERHADAP ANGKA KEJADIAN DEMAM BERDARAH DENGUE DI DUSUN PESALAKAN DESA PEJENG KANGIN - I Putu Artha Wijaya; Alfiery Leda Kio; Dewa Gede Dharma Suasta (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2021)
Dengue Hemorrhagic Fever is a contagious disease caused by the dengue virus. The clinical manifestations of dengue hemorrhagic fever include bleeding that causes shock that leads to death. One of the controls for dengue hemorrhagic fever that can be carried out by all ages and from all levels of education is the activity of eradicating mosquito nests (PSN). Satu Rumah Satu Jumantik is a community participation in controlling vector-borne diseases, especially dengue fever through the 3M Plus PSN. This study aims to determine